2022
DOI: 10.20525/ijfbs.v11i1.1668
|View full text |Cite
|
Sign up to set email alerts
|

Company Value Impact on Capital Structure, Sales Growth, and Company Size

Abstract: The objective of this study is to understand the influence of capital structure, sales growth and firm size on firm value in the automotive and component sub-sectors that are registered on the Indonesia Stock Exchange during 2016-2020 period. The research method used in this research is descriptive and verification methods. The findings of the study state that capital structure significantly and positively influences firm value, while there is no effect of sales growth and firm size on firm value in the automo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
0
0
1
Order By: Relevance
“…Therefore, the debt will decrease by itself. This result is in line with the results of previous research conducted by Hertina et al (2022), Haron et al (2021), Pathak &Chandani (2021), andRani et al (2020) who found that liquidity has a negative effect on capital structure.…”
Section: Effect Of Liquidity (Cr) On Capital Structuresupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, the debt will decrease by itself. This result is in line with the results of previous research conducted by Hertina et al (2022), Haron et al (2021), Pathak &Chandani (2021), andRani et al (2020) who found that liquidity has a negative effect on capital structure.…”
Section: Effect Of Liquidity (Cr) On Capital Structuresupporting
confidence: 92%
“…Companies that have high liquidity mean that they can pay short-term debt, so they tend to reduce total debt, which in turn will make the capital structure smaller. Previous research conducted by Hertina et al (2022), Haron et al (2021), Pathak &Chandani (2021), andRani et al (2020) state that liquidity has a negative effect on capital structure. Based on the results of the description and previous research, the hypothesis is proposed as follows:…”
Section: Liquiditymentioning
confidence: 94%
See 1 more Smart Citation
“…Sumarau's [18] results study shows investment, funding decisions, and profitability simultaneously affect firm value, while partially only funding and profitability decisions influence firm value. Hertina, et al research results [19] show capital structure, and liquidity ratios have an effect, while company growth has no effect firm value .…”
Section: Introductionmentioning
confidence: 94%
“…Rasio leverage dipergunakan sebagai tolak ukur seberapa jauh aktiva perusahaan dibiayai dengan utang, yang berarti total liabilitas yang dipergunakan perusahaan dalalm membiayai usahanya daripada menggunakan modal sendiri (Prawira & Sandria, 2021). Riset yang menggunakan leverage (seperti: Dianti et al, 2020;Hertina et al, 2019;Kalbuana et al, 2020;Naelly & Mustafa, 2020;Pattiruhu & Paais, 2020;Salim & Wahyuni, 2020). Leverage dalam riset ini diprosikan DER (Debt to Equity Ratio) menggunakan formula hutang jangka panjang dibagi total asset.…”
Section: Variabel Eksogen: Leverage (X1)unclassified